EVALUATION OF USED EXUDATIVE IRRIGATION TUBES AND DRIP IRRIGATION FOR SOME SOIL WATER PARAMETERS AND CONSUMPTIVE USE OF CUCUMBER - & et al., Aldulaimy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiment was conducted during the spring season of 2017 at AL-Ramadi district, AL-Anbar Governorate, Iraq. The research was conducted in a silty Loam soil, to evaluate of the performance and used exudative irrigation tubes for previous season compared to drip irrigation in some hydraulic parameters: Irrigation systems, moisture distribution, Application efficiency cucumber crop factor of the and cucumber yield. The experiment was conducted according to randomized complete block design (RCBD) with three replicates. Results showed an increase in uniformity coefficient at drip irrigation as it reached 97% compared with 96.2% for exudation, with variation percentage of 8.33% for drip irrigation and 11.32% for irrigation of exudative. Moisture content decreased with distance from emitters horizontally for the three growth stages and irrigation methods. Cucumber water consumptive use was 356.32 mm for exudative irrigation compared with 456.6 mm for drip irrigation with decrease 21.96 %. Exudative irrigation method significantly increased in WUE as it reached to 15.29 kg m-3 compared with 13.13 kg m-3 for drip irrigation with an increase of 12.82%. The result showed an increment in irrigation efficiency giving 89.12% for drip irrigation compared with 85.88% for exudative irrigation with an increase 3.64%. The crop factor was 0.61, 0.66, 0.77, and 0.51 for the initial vegetative growth stage, second vegetative growth stage, start of flowering and fruit set and end flowering and fruit set respectively.